THE INFLUENCED OF LEARNING ANXIETY AND METACOGNITIVE STRATEGIES ON STUDENTS’ LISTENING COMPREHENSION ACHIEVEMENT - Mulyani, Destia Dwi; Elsaviana, Maria Octa (Esteem Journal of English Education Study Programme, 2025)
This study aimed to examine three key areas: (1) whether there was a significant interaction between the application of metacognitive strategies and levels of listening anxiety on students’ listening comprehension outcomes; (2) whether students’ listening performance varied significantly across different anxiety levels namely high, moderate, and low; and (3) the extent to which specific aspects of listening contributed to overall comprehension achievement. Employing a factorial design that included both experimental and control groups, the study engaged sixty participants equally distributed between the two groups. The experimental group, which received targeted instruction in metacognitive listening strategies, demonstrated marked gains in listening comprehension. A significant interaction effect was identified between metacognitive strategy use and listening anxiety, indicating that the effectiveness of strategy application varied with anxiety levels. Notably, within the experimental group, statistically significant differences in listening performance emerged between students with high and low anxiety, as well as between those with moderate and low anxiety—particularly in the domains of identifying main ideas, recalling details, and drawing inferences. Among the assessed listening components, the ability to grasp details proved to be the strongest predictor of listening comprehension achievement, followed sequentially by identifying main ideas, making inferences, and interpreting the overall message.